2020
DOI: 10.1017/s1463423620000183
|View full text |Cite
|
Sign up to set email alerts
|

Results of hearing screening of school-age children in Bishkek, Kyrgyzstan

Abstract: Aim: To gauge the prevalence of hearing loss in school children in Bishkek, Kyrgyzstan, and refer pupils with positive results for further diagnostic testing. Background: According to WHO data, hearing disorders are common in school-age children. Screening for hearing loss is an important preventative tool, helping to avoid further complications. Expenditure that supports early child development can reduce future outlay on health care and social services; it can eliminate disability prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 34 publications
0
17
2
7
Order By: Relevance
“…In comparison, the prevalence of hearing loss children attending rural schools and small towns throughout Poland has been estimated as 16.4% [ 22 ]. Data from pilot hearing screening projects, conducted by the Institute of Physiology and Pathology of Hearing in various African countries, have shown the prevalence of hearing loss (18–34%) [ 29 ], and in Asian countries the prevalence is 15.9–24.1% [ 21 , 26 ]. For comparison, the percentage of children in India with hearing loss was found to be 11.9% (more than 1 in 8 children) [ 30 ], and in Iran it was found that 10% of children aged 7–8 years old may have a hearing problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, the prevalence of hearing loss children attending rural schools and small towns throughout Poland has been estimated as 16.4% [ 22 ]. Data from pilot hearing screening projects, conducted by the Institute of Physiology and Pathology of Hearing in various African countries, have shown the prevalence of hearing loss (18–34%) [ 29 ], and in Asian countries the prevalence is 15.9–24.1% [ 21 , 26 ]. For comparison, the percentage of children in India with hearing loss was found to be 11.9% (more than 1 in 8 children) [ 30 ], and in Iran it was found that 10% of children aged 7–8 years old may have a hearing problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss was defined as a pure-tone average higher than 20 dB in at least one of the following pure-tone averages: four-frequency pure-tone average (FFPTA), high-frequency pure-tone average (HFPTA), and low-frequency pure-tone average (LFPTA). Firstly, speech relevant hearing loss was defined as the four-frequency pure-tone average (FFPTA) at 0.5, 1, 2, and 4 kHz at a value for a threshold of >20 dB [ 25 , 26 ]. HFPTA were defined as a pure-tone average above 2 kHz (4 and 8 kHz) [ 22 , 27 ] and LFPTA at 0.5, 1, 2 kHz [ 24 , 28 ] at a value for a threshold of >20 dB HL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each ear separately, air conduction thresholds at conventional octave frequencies from 0.5 to 8 kHz were determined with the same paradigms as in a previous study [ 27 , 29 , 32 ] as well as at half-octave frequencies of 3 and 6 kHz. Measurements at 125 and 250 Hz were omitted as being less useful and vulnerable to noise disturbance [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Screening pure tone audiometry was conducted in a quiet room allocated by the school headmaster. The examination was performed on the Platform for Sensory Organs Examination [27,29,30] connected to the "SZOK" ® central database [31]. The system is based on a powerful central computer with multiple portable computers communicating with it via the Internet.…”
Section: Audiometric Testingmentioning
confidence: 99%